2022
DOI: 10.1002/ail2.65
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning to predict power output from respiratory inductive plethysmography data

Abstract: Power output is one of the most accurate methods for measuring exercise intensity during outdoor endurance sports, since it records the actual effect of the work performed by the muscles over time. However, power meters are expensive and are limited to activity forms where it is possible to embed sensors in the propulsion system such as in cycling. We investigate using breathing to estimate power output during exercise, in order to create a portable method for tracking physical effort that is universally appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In [39], the authors found the limits of agreement of RIP with spirometry to be too high (≥20%) to validate RIP in obese people. The studies [36,41,42,52,[56][57][58][60][61][62][63]91] implemented machine learning and expressed their results in terms of accuracy, precision, sensitivity, specificity, and/or Cohen's kappa figures. The resultant figures were self-explanatory in terms of statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [39], the authors found the limits of agreement of RIP with spirometry to be too high (≥20%) to validate RIP in obese people. The studies [36,41,42,52,[56][57][58][60][61][62][63]91] implemented machine learning and expressed their results in terms of accuracy, precision, sensitivity, specificity, and/or Cohen's kappa figures. The resultant figures were self-explanatory in terms of statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Power output during exercise was studied in [60] with various predictive models, which showed moderate accuracy (R 2 = 0.56, mean absolute percentage error: 0.20-0.24) and need improvement. However, the fact that the data were obtained from a single subject is the greatest limitation of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Helge has commissioned an article entitled ‘ Deep learning to predict power output from respiratory inductive plethysmography data ’ 1 . As we move into an age where our own personal health data are becoming increasingly important to personalise our lifestyles, including exercise regimes, there is a new scrutiny being placed on the equipment, which is required to generate these data.…”
mentioning
confidence: 99%